2014
DOI: 10.1155/2014/838162
|View full text |Cite
|
Sign up to set email alerts
|

GC Analyses of Salvia Seeds as Valuable Essential Oil Source

Abstract: The essential oils of seeds of Salvia verbenaca, Salvia officinalis, and Salvia sclarea were obtained by hydrodistillation and analyzed by gas chromatography (GC) and GC-mass spectrometry. The oil yields (w/w) were 0.050, 0.047, and 0.045% in S. verbenaca, S. sclarea, and S. officinalis, respectively. Seventy-five compounds were identified. The essential oil composition of S. verbenaca seeds showed that over 57% of the detected compounds were oxygenated monoterpenes followed by sesquiterpenes (24.04%) and labd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Essential oil of Salvia aethiopi and Salvia nemorosa also contained high concentrations of β-caryophyllene (24.8% and 19.03% for each plant) [17]. In the essential oil from Salvia verbenaca , caryophyllene oxide was the main component with 7.28% [20]. According Liu et al For Salvia umbratica , had a caryophyllene oxide concentration of 8.42% [12].…”
Section: Resultsmentioning
confidence: 99%
“…Essential oil of Salvia aethiopi and Salvia nemorosa also contained high concentrations of β-caryophyllene (24.8% and 19.03% for each plant) [17]. In the essential oil from Salvia verbenaca , caryophyllene oxide was the main component with 7.28% [20]. According Liu et al For Salvia umbratica , had a caryophyllene oxide concentration of 8.42% [12].…”
Section: Resultsmentioning
confidence: 99%
“…The terpenoids contained in the essential oils of S. verbenaca L. mostly consist of α -pinene, β -pinene, sabinene, 1,8-cineole, β -phellandrene, linalool, p-cymene, linalyl acetate, E- β -ocimene, (Z)- β -ocimene, tricyclene, camphor, 1,10-di-epi-cubenol, epi-13-manool, cis-muurola-3,5-diene, δ -selinene, trans -sabinene hydrate acetate, β -caryophyllene, viridiflorol, and germacrene D [ 31 – 33 ] ( Table 1 , Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oxygenated monoterpenes controlled the production and emission of flowering components, including preflowering buds, fully grown flowers, and petals. Also, Taârit et al [ 33 ] showed that the major compounds in EOs in Salvia aerial parts from the three Algerian regions were the monoterpene hydrocarbons and oxygenated sesquiterpenes. Additionally, the influence of collecting locations and phenophases on the production and chemical composition of S. verbenaca L. essential oils was examined by Farhat et al [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations